Periodic Upright Nanopyramids for Light Management Applications in Ultrathin Crystalline Silicon Solar Cells - Wang, Puqun; Liu, Zhe; Xu, Kaichen; Blackwood, Daniel John; Hong, Minghui; Aberle, Armin G.; Stangl, Rolf; Peters, Ian Marius (IEEE Journal of Photovoltaics, 2017)
Motivated by the primary benefit of reduced material cost, the thickness of crystalline silicon solar cells has been continuously reduced. Laboratory and industrial studies have explored ultrathin crystalline silicon solar cells below 50 μm with ambitious endeavors toward thicknesses of only a few micrometers. Ultrathin crystalline silicon solar cells require compatible small-scale surface textures to enhance the optical absorption. For this purpose, a novel submicron periodic nanostructure -periodic upright nanopyramids (PuNPs) -is fabricated by an integrated process of laser interference lithography and anisotropic etching of silicon in an alkaline solution. By simulation and measurements, we demonstrate that PuNPs are able to reduce front surface reflectance more effectively than conventional micron-scale pyramid textures and previously investigated periodic inverted nanopyramids (PiNPs). With a silicon nitride antireflection coating, we predict that PuNPs reduce the front surface reflectance to below 1% at an angle of incidence of 8°, which is comparable to black silicon. The superior antireflective property of PuNPs contributes to an absorbed photocurrent density of 40.8 mA/cm2 for a 40 μ m silicon absorber layer, which is 0.7 mA/cm2 higher than PiNPs, 0.8 mA/cm2 higher than inverted pyramids and 1 mA/cm2 higher than upright pyramids.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Light management; periodic nanostructures; ultrathin silicon solar cells